CYTOMORPHOLOGICAL CHANGES IN THE LYMPHOCYTE POPULATION AS AN ADDITIONAL DIFFERENTIAL DIAGNOSTIC CRITERION OF ATYPICAL PNEUMONIA - Raksha-Slyusareva, O.A.; Trichlib, V.I.; Slyusarev, O.A.; Zadorozhna, V.I.; Kovalenko, P.G. (World of Medicine and Biology, 2024)
Cytomorphological changes in the lymphocyte population were determined to obtain additional criteria for the differential diagnosis of atypical pneumonia and acute respiratory diseases in the first days of illness. The research was conducted among a mobilized individuals and contract military servicemen. Among 84 were patients with acute respiratory diseases, 65 with atypical pneumonia, and 150 conditionally healthy individuals aged 19 to 45 years. The research established differences in cytomorphological changes in the lymphocyte population in atypical pneumonia and acute respiratory diseases in the early days of the illness, reflecting the features of the pathogenesis of these diseases at the immune system level. As additional differential diagnostic criteria for atypical pneumonia and acute respiratory diseases in the early days of illness, the following indicators can be applied: the content of lymphocytes in the form of Botkin-Gumprecht shadows, which is likely higher in acute respiratory diseases, and immune system insufficiency, which reaches 100 % in atypical pneumonia but is lower in acute respiratory diseases.